Learning art in primary education through quick response (QR) Codes - Seva Soriano, Elia (2018)
This paper outlines the possibilities of using QR codes for both learning and teaching Art History in primary education. The Project Based Learning was used. This approach fulfills three purpose regarding students: they gained scientific knowledge, they put on practice collaborative learning and they integrate technology. The study was carried out on a sample of 24 primary school students, aging between 10 and 11. Initial and final questionnaires and a rubric to check behavior were used to assess the learning progress. The results were highly satisfactory regarding the improvement of Art knowledge, the successful collaborative work among peers and the profuse use of technology. Students improved, both quantitatively and qualitatively, their conceptual, procedural and attitudinal knowledge.